Pengaruh Marketing Mix Syariah Berbasis Digital Terhadap Kepuasan Konsumen Pada Platform E-Commerce (Studi Kasus Mahasiswa FEB Institut Bisnis Muhammadiyah Bekasi) - Anto Apriyanto; Muhammad Oksa Bachtiar (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of sharia-based digital marketing mix on consumer satisfaction on e-commerce platforms, particularly among students of the Faculty of Economics and Business, Institut Bisnis Muhammadiyah Bekasi. The rapid development of digital technology has encouraged the transformation of marketing practices toward digital channels; however, the integration of sharia principles in digital marketing strategies remains limited. This research employs a quantitative approach with an associative design. The population consists of 250 students, with a sample of 71 respondents determined using the Slovin formula and selected through incidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS version 26. The results indicate that the sharia-based digital marketing mix has a positive and significant effect on consumer satisfaction, as evidenced by a t-value of 4.053 with a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) shows that 19.2% of consumer satisfaction is explained by the sharia-based digital marketing mix, while the remaining 80.8% is influenced by other factors outside the model. These findings suggest that the implementation of sharia principles such as honesty, transparency, fairness, and trustworthiness in digital marketing contributes to enhancing consumer satisfaction on e-commerce platforms.